2011
DOI: 10.2478/v10176-011-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-solvent sonocrystallisation of lactose

Abstract: The present work deals with ultrasound assisted crystallisation of lactose from lactose solution. The crystallisation of lactose was completed rapidly by applying the ultrasound waves in the presence of an anti-solvent (n-propanol), at the room temperature (30±3 o C). The yield of lactose was found to be more than 85% (w/w) in 4 minutes of sonication. The spread of the crystal size distribution was found to decrease with increase in sonication time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…This disagreed with the previous statements that cavitation caused by power ultrasound affects the crystallization processing. For the crystallization in supersaturated liquid, Li and others () observed that a certain size of crystals is increased after employing the power ultrasound, which was contradictory when previous findings showing that the sizes of crystals were smaller with applying power ultrasound (Suzuki and others ; Patel and Murthy ).…”
Section: Acoustic Mechanisms Of Power‐ultrasound‐assisted Crystallizamentioning
confidence: 80%
See 1 more Smart Citation
“…This disagreed with the previous statements that cavitation caused by power ultrasound affects the crystallization processing. For the crystallization in supersaturated liquid, Li and others () observed that a certain size of crystals is increased after employing the power ultrasound, which was contradictory when previous findings showing that the sizes of crystals were smaller with applying power ultrasound (Suzuki and others ; Patel and Murthy ).…”
Section: Acoustic Mechanisms Of Power‐ultrasound‐assisted Crystallizamentioning
confidence: 80%
“…Innovative methods like ultrasound‐assisted freezing (UAF), high‐pressure‐assisted freezing, and electrostatic assisted freezing (Woo and Mujumdar ) can have a better control of the crystallization process and improve crystal formation rate (Lakshmisha and others ; Norton and others ). For supersaturated crystallization, the crystallization process is slow (Raghavan and others ; Patel and Murthy ) and difficult to control. Although with the demand for different products, the conventional methods are optimized to achieve better crystallization results (Hartel and Shastry ), novel methods are also developed to better manage the crystallization process.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nonsolvent compounds into whey concentrate (antisolvent crystallization) decreases the solubility of lactose, narrows the metastable zone, and reduces the induction times of nucleation. In general, the antisolvent crystallization improves the yield of crystallization and reduces the size of lactose crystals [20,32]. The main drawbacks of antisolvent crystallization are the large amounts of solvent used, and the expensive separation and purification steps required to remove the antisolvent from the product [5,9].…”
Section: Conventional Recovering Of Lactose From Wheymentioning
confidence: 99%
“…It has already been discussed that sonication favors the formation of supersaturation and modifies the metastable zone [13,14,30]. The effect of ultrasound on lactose supersaturation has been scarcely documented chiefly because almost all the studies on lactose sonocrystallization have been done in combination with nonsolvents that greatly modify the solubility of lactose (Table 1) [4,9,18,20,28,32]. The antisolvents used for these studies include ethanol, propanol, glycerol, and acetone, all of which decrease the solubility of lactose sharply and speed up the attainment of supersaturation [5].…”
Section: Effects On Lactose Supersaturation and Nucleationmentioning
confidence: 99%
See 1 more Smart Citation